The Performance Impact of Management Control Systems: Assessing the Mediating Role of Organizational Culture - Lyu, Chunchun; Swatdikun, Trairong; Lakkanawanit, Pankaewta; Issayeva, Gulmira (Emerging Science Journal, 2025)
This research examines the dual-pathway impact of Management Control Systems (MCS) on Company Performance (CP) in China’s liquor industry, with a focus on the mediating role of Organizational Culture (OC). The research aims to address gaps in understanding how MCS enhances both financial and non-financial performance through cultural mechanisms, a critical yet underexplored dynamic in heritage-based industries. Employing a mixed-methods approach, the research analyzes survey data from 497 firms using Structural Equation Modeling (SEM) and mediation analysis to test three hypotheses: (1) MCS directly improves CP, (2) MCS fosters OC, and (3) OC mediates the MCS-CP relationship. Key findings reveal that MCS significantly boosts CP (β=0.438, p<0.001), while OC partially mediates this relationship (indirect effect β=0.249, p<0.001). The novelty lies in demonstrating how MCS transcends operational efficiency to shape cultural assets, which in turn drive competitive advantage. This research advances contingency theory by highlighting sector-specific adaptations, such as digital MCS tools balancing tradition with market responsiveness, and offers practical insights for integrating control systems with cultural stewardship in traditional industries.